Subjective sleep disturbances and glycemic control in adults with long-standing type 1 diabetes: The Pittsburgh's Epidemiology of Diabetes Complications study. (September 2016) - Denic-Roberts, Hristina; Costacou, Tina; Orchard, Trevor J.
Abstract: Aims: To date, studies on sleep disturbances in type 1 diabetes (T1D) have been limited to youth and/or small samples. We therefore assessed the prevalence of subjective sleep disturbances and their associations with glycemia and estimated insulin sensitivity in individuals with long-standing T1D. Methods: We conducted a cross-sectional study including 222 participants of the Epidemiology of Diabetes Complications study of childhood-onset T1D attending the 25-year examination (mean age = 52 years, diabetes duration = 43 years). The Berlin Questionnaire (risk of obstructive sleep apnea, OSA), the Epworth Sleepiness Scale (daytime sleepiness), and the Pittsburgh Sleep Quality Index (sleep quality, bad dreams presence, and sleep duration) were completed. Associations between sleep disturbances and poor glycemic control (HbA1c  ⩾ 7.5%/58 mmol/mol), log-transformed HbA1c, and estimated insulin sensitivity (estimated glucose disposal rate, eGDR, squared) were assessed in multivariable regression. Results: The prevalences of high OSA risk, excessive daytime sleepiness, poor sleep quality, and bad dreams were 23%, 13%, 41%, and 26%, respectively, with more women (51%) reporting poor sleep quality than men (30%, p  = 0.004). Participants under poor glycemic control were twice as likely to report bad dreams ( p  = 0.03), but not independently ( p  = 0.07) of depressive symptomatology. Sleep duration was directly associated with HbA1c among individuals with poor glycemic control, but inversely in their counterparts (interaction p  = 0.002), and inversely associated with eGDR ( p  = 0.002). Conclusions: These findings suggest important interrelationships between sleep, gender, depressive symptomatology, and glycemic control, which may have important clinical implications. Further research is warranted to examine the mechanism of the interaction between sleep duration and glycemic control.